Factors Contributing to Low Utilization of Pit Latrines among Community Households in Muyongwe Sector, Gakenke District-Rwanda - Mutagugumba, Clement; Silali, Maurice B. (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Access to adequate sanitation remains a critical public health concern in many rural communities of Rwanda. Despite the widespread construction of pit latrines in Muyongwe Sector, their utilization rates remain notably low. This study aimed to identify and analyze the factors contributing to the low utilization of pit latrines in Muyongwe Sector Zone. A mixed-methods approach was employed, combining quantitative household surveys with qualitative interviews and field observations. Data were collected from 328 households selected through systematic simple random sampling. The findings revealed that socio-economic factors such as low-income levels, limited awareness, poor hygiene practices, and cultural beliefs significantly influence latrine use. Structural issues including poor latrine design, lack of privacy, and inadequate maintenance also contributed to low utilization. Additionally, environmental challenges such as soil instability and flooding were found to discourage proper latrine use. Chi-square analysis confirmed a highly significant association between latrine hygiene and utilization (χ² = 42.4, df = 1, p < 0.0001). Similarly, latrine location significantly influenced the use, with easily accessible latrines being more utilized than those in difficult-to-reach locations (χ² = 4.58, df = 1, p = 0.04). The study concludes that improving community education on sanitation, enhancing the quality and durability of latrine construction, and promoting community-based monitoring systems are essential to increasing utilization rates. The findings provide valuable insights for policymakers and development partners working to improve rural sanitation practices and achieve national health and hygiene goals.